Stunting Management Monitoring System - Jannah, Helmi Roichatul; Kusumadewi, Sri; Fitriyanto, Raden Edi (Sinkron : jurnal dan penelitian teknik informatika, 2021)
Stunting is one of the chronic nutritional problems in which the length or height of children is shorter than normal children their age. In the short term, stunting can interfere with brain and physical development, while in the long term, stunting can reduce a person's cognitive abilities and intelligence, as well as being susceptible to various diseases. Stunting cannot be cured, but it can be optimized for growth and development during the 1000 first days (first day of life) by routinely carrying out examinations. This is the goal of this study, namely to build a system that can monitor the health of pregnant women and toddlers aged 0-24 months in an effort to optimize the growth and development of stunting children. Stunting management monitoring system is carried out based on certain nutritional status management which indicates the birth of a child experiencing stunting. The system is built in the form of a website, where expert rules related to the management of nutritional status are translated into the system using the Rule Based Reasoning method. To measure the success of the system, usability testing or functional testing by users is carried out with the attributes of testing the ease of use of the system and the ease of the system to learn. Overall, the Stunting management monitoring system can accommodate the early stages of health monitoring in 1000 first days, however, development will continue in line with user needs.